PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA PT. HASTEX BERBASIS WEB - Yusuf Yusuf; Lisana Lisana; Hendra Dinata (Perpustakaan Universitas Surabaya, 2018)
PT Hastex is a company engaged in the production and sales of Muslim clothing. Activities undertaken by PT Hastex in its business process is to produce Muslim fashion or buy Muslim fashion so from the supplier and resell it. Currently the transaction process conducted by PT Hastex still using Microsoft Excel starting from the process of purchasing, sales, production of Muslim fashion, the process of repayment of debt / accounts receivable and other processes. From the system there are some problems that are mistakes - mistakes in making financial statements, errors in the management of both the finished goods stock and raw materials, and PT Hastex difficulties in conducting the search previous reports. Therefore, a web based accounting information system is created to assist PT Hastex in carrying out its purchasing, sales and other activities. Making this information system is expected to minimize errors that may occur when running business activities. The data related to all PT Hastex business activities will be stored in the database. The data will be processed in order to become appropriate and efficient financial reports. At the verification stage, PT Hastex conducts trials on information systems created to be free from errors. And in the validation phase, interviewed to the accountant, PPIC staff and managers of PT Hastex to ensure the information system created is in accordance with the needs of the company.